Analisis Efikasi Diri Dan Respon Siswa Dalam Penggunaan Model E Learning Berbasis Google Classroom - Zaenal Wathon; Sholeh Hidayat; Luluk Asmawati (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2021)
This study aims to: 1) analyze students' self-efficacy in using the e-learning model with the google classroom application on Civics Education subjects at SMPN 3 Cigemblong, 2) analyze student responses in e-learning with the google classroom application on PPKN subjects at SMPN 3 Cigemblong, and 3) analyzing students' self-efficacy and responses to the e-learning model based on google classroom on Civics education subjects at SMPN 3 Cigemblong. The method used in this study is a qualitative method with a phenomenological approach. The phenomenological approach relates to the understanding of students' daily life and the intersubjective world (world of life) in the learning process during a pandemic. The subjects of this study were class VIII students, principals and representatives of parents. while the source of data taken from the student element is as many as 22 students and the number of students at SMPN 3 Cigemblong is 215 students. During the study found three groups of respondents. 1) respondents with high efficacy with good responses during online learning, 2) respondents with medium efficacy with mediocre and stagnant responses, 3) respondents with low efficacy, with apathetic, indifferent and lazy responses to online learning tasks. Thus, the conclusion is, that e learning with Google Classroom there are still students who are unprepared and have not been able to adapt to Google Classroom learning, so that students' efficacy and responses fluctuate depending on the subjects they like, in terms of Civics education subjects as a whole almost most students have positive efficacy and response and only a small proportion have low efficacy and response in doing online assignments. Keywords: self-efficacy, google classroom, civic education Penelitian ini bertujuan untuk: 1) menganalisis efikasi diri siswa dalam penggunaan model e learning dengan aplikasi google classroom pada mata pelajaran PPKN di SMPN 3 Cigemblong, 2) menganalisis respon siswa dalam e learning dengan aplikasi google classroom pada mata pelajaran PPKN di SMPN 3 Cigemblong, dan 3) menganalisis efikasi diri dan respon siswa terhadap model e learning berbasis google classroom pada mata pelajaran PPKn di SMPN 3 Cigemblong. Metode yang digunakan dalam penelitian ini adalah metode kualitatif dengan pendekatan fenomenologi. Pendekatan fenomenologi berhubungan dengan pemahaman tentang kehidupan keseharian dan dunia intersubjektif (dunia kehidupan) siswa dalam proses pembelajaran di masa pandemi. Subjek penelitian ini adalah siswa dan siswi kelas VIII, kepala sekolah dan perwakilan orangtua. sedangkan sumber data yang diambil dari unsur siswa adalah sebanyak 22 orang siswa dan siswi dari jumlah siswa di SMPN 3 Cigemblong sebanyak 215 siswa. Selama penelitian ditemukan tiga kelompok responden. 1) responden dengan efikasi tinggi dengan respon yang baik selama belajar online, 2) responden dengan efikasi menengah dengan respon yang biasa saja dan stagnan, 3) responden dengan efikasi rendah, dengan respon apatis, acuh dan malas pada tugas belajar online. Dengan demikian kesimpulannya adalah, bahwa pembelajaran e learning dengan google classroom masih terdapat siswa dengan ketidaksiapan dan belum bisa menyesuaikan diri dengan pembelajaran google classroom, sehingga efikasi dan respon siswa bersifat fluktuatif tergantung dengan mata pelajaran yang mereka sukai, dalam hal mata pelajaran PPKn secara keseluruhan hampir sebagian besar siswa memiliki efikasi dan respon yang positif dan hanya sebagian kecil yang memiliki efikasi dan respon yang rendah dalam mengerjakan tugas online. Kata kunci: efikasi diri, google classroom, PPKn